What is gluten? - Biesiekierski, Jessica R (Journal of gastroenterology and hepatology, 2017)
Gluten is the main storage protein of wheat grains. Gluten is a complex mixture of hundreds of related but distinct proteins, mainly gliadin and glutenin. Similar storage proteins exist as secalin in rye, hordein in barley, and avenins in oats and are collectively referred to as “gluten.” The objective was to discuss the biochemical and functional properties of the gluten proteins, including structure, sources, and dietary intakes. Literature was reviewed from food science and nutrition journals. The gluten protein networks vary because of different components and sizes, and variability caused by genotype, growing conditions, and technological processes. The structures and interactions of this matrix contribute to the unique properties of gluten. The resulting functions are essential to determining the dough quality of bread and other baked products. Gluten is heat stable and has the capacity to act as a binding and extending agent and is commonly used as an additive in processed foods for improved texture, moisture retention, and flavor. Gliadin contains peptide sequences that are highly resistant to gastric, pancreatic, and intestinal proteolytic digestion in the gastrointestinal tract. The average daily gluten intake in a Western diet is thought to be 5–20 g/day and has been implicated in several disorders. Gluten containing grains (wheat, rye, barley, and oats) are important staple foods. Gluten is among the most complex protein networks and plays a key role in determining the rheological dough properties.